2009
DOI: 10.1161/hypertensionaha.109.130237
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Mechanisms and Mediators of the Effects of Air Pollution Exposure on Blood Pressure and Vascular Function in Healthy Humans

Abstract: Fine particulate matter air pollution plus ozone impairs vascular function and raises diastolic blood pressure. We aimed to determine the mechanism and air pollutant responsible. The effects of pollution on heart rate variability, blood pressure, biomarkers, and brachial flow-mediated dilatation were determined in 2 randomized, double-blind, cross-over studies. In Ann Arbor, 50 subjects were exposed to fine particles (150 μg/m3) + ozone (120 ppb) for 2 hours on 3 occasions with pretreatments of an endothelin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
345
7
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 429 publications
(390 citation statements)
references
References 37 publications
32
345
7
6
Order By: Relevance
“…Our data represented that DENPs caused neutrophil influxinto the heart tissue enhanced epithelial permeability in rats [36]. To the best of our knowledge no study till date has demonstrated the effect of quercetinon the cardiovascular parameters following DENP exposure.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our data represented that DENPs caused neutrophil influxinto the heart tissue enhanced epithelial permeability in rats [36]. To the best of our knowledge no study till date has demonstrated the effect of quercetinon the cardiovascular parameters following DENP exposure.…”
Section: Discussionsupporting
confidence: 59%
“…Our experimental results corroborate with previous findings which illustrated that long exposures to PM air pollution caused the influx of cytokines leading to systemic inflammation. Simultaneously, the markers for oxidative damage were also elevated [36,37]. In the current study, and we have determined the effect of DENPs on platelet numbers and all blood content.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, only the variable for the use of any antihypertensive medication (yes/no) was used in the final models. We also studied the possible confounding effect of ozone, because even though the association between ozone and blood pressure is not evident, [29,30] some studies have suggested ozone exposure has an effect on blood pressure [25]. The influence of extreme temperatures on our associations was studied by excluding 2.5% of the hottest and coldest temperatures from the analyses, and we did visual inspection of the linearity of the association between temperature and blood pressure using plots created by penalized spline models, using the generalized additive mixed model (gamm) function in R.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Some research has suggested a direct influence of air pollution on health measurements in healthy subjects, such as heart rate elevation and an increase in systolic blood pressure [10]. Some results provide evidence that an increased level of air pollution may lead to detectable adverse effects on the cardiovascular systems of healthy young individuals, such as constriction of blood vessels [11]. The present study evaluated the association between air pollution and changes in heart rate variability as a marker of cardiac autonomic dysfunction in healthy individuals, and also determined the frequency of cardiac arrhythmias and QT interval changes during polluted compared to unpolluted days in Tehran, a city associated with high exposure to air pollutants.…”
Section: Introductionmentioning
confidence: 99%